Youtube dan Perbankan Syariah - Rahman, Muthia (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2022)
The purpose of this research was to investigate how students majoring in subjects other than English, at the Syaria Banking Department in STES Manna Wa Salwa Tanah Datar Sumatera Barat, use social media, particularly YouTube, and to determine the impact it has on their speaking skills. The study was carried out using a descriptive qualitative design, with 25 participants selected from the Syaria Banking Department. The students were asked to speak on prepared topics in front of a phone camera, and five online meetings were held to assess their progress. A semi-structured interview was also conducted to gather more detailed supporting data. The findings indicate that using social media, particularly YouTube, had a positive impact on the speaking ability of non-English major students, as evidenced by iswsissefforts to improve their speaking skills, such as psychological factors (e.g. lack of motivation and confidence), environmental factors (e.g. relationship with their surroundings), and linguistic factors (e.g. finding references, selecting vocabulary, and using appropriate speaking style and gestures). The use of social media, especially YouTube, was found to be helpful in overcoming these obstacles and improving students' speaking ability.